Will the Bacteria Survive in the CeO(2) Nanozyme-H(2)O(2) System? - Zhu, Weisheng (Molecules, 2021)
As one of the nanostructures with enzyme-like activity, nanozymes have recently attracted extensive attention for their biomedical applications, especially for bacterial disinfection treatment. Nanozymes with high peroxidase activity are considered to be excellent candidates for building bacterial disinfection systems (nanozyme-H(2)O(2)), in which the nanozyme will promote the generation of ROS to kill bacteria based on the decomposition of H(2)O(2). According to this criterion, a cerium oxide nanoparticle (Nanoceria, CeO(2), a classical nanozyme with high peroxidase activity)-based nanozyme-H(2)O(2) system would be very efficient for bacterial disinfection. However, CeO(2) is a nanozyme with multiple enzyme-like activities. In addition to high peroxidase activity, CeO(2) nanozymes also possess high superoxide dismutase activity and antioxidant activity, which can act as a ROS scavenger. Considering the fact that CeO(2) nanozymes have both the activity to promote ROS production and the opposite activity for ROS scavenging, it is worth exploring which activity will play the dominating role in the CeO(2)-H(2)O(2) system, as well as whether it will protect bacteria or produce an antibacterial effect. In this work, we focused on this discussion to unveil the role of CeO(2) in the CeO(2)-H(2)O(2) system, so that it can provide valuable knowledge for the design of a nanozyme-H(2)O(2)-based antibacterial system.